Application of ERAS concept in clinical nursing of patients with advanced cancer pain of gynecological malignant tumors - Liao, Haijing; Lei, Yuanxiu (Frontiers in Oncology, 2023)
Gynecological malignant tumors refer to malignant tumors of organs and tissues centered on the uterus, ovaries, and fallopian tubes. Among gynecological tumors, endometrial cancer is the most malignant, accounting for more than 80% of malignant tumors in the female reproductive tract. Common symptoms are vaginal bleeding and pain. This article aims to explore the application and analysis of the concept of ERAS (Enhanced Recovery After Surgery) in the clinical care of patients with advanced cancer pain from gynecological malignancies. ERAS aims to reduce complications, shorten hospitalization time, reduce medical costs, and enable patients to recover quickly by adopting a series of perioperative management measures for patients. This article analyzes the pain caused by late-stage cancer, proposes an ERAS multimodal analgesia method, and uses image fusion technology to detect cancer patients. This article finally conducts an experimental exploration of the clinical nursing of the ERAS concept in the treatment of advanced cancer pain in gynecological malignancies. The results of this study showed that in terms of pain impact score, before treatment, the score of group M was 39.07 and the score of group N was 38.92, and the difference was not statistically significant. The score after ERAS concept treatment was 58.14, and the score after traditional treatment was 43.79, with a significant difference. Research shows that the pain impact score after treatment is significantly better than before treatment, and the improvement effect of ERAS concept treatment is more obvious.